Research prospects for kidney xenotransplantation: a bibliometric analysis - Shujun Yang; Mingtao Zhang; Hao Wei; Bin Zhang; Jiang Peng; Panfeng Shang; Shengkun Sun (Renal Failure)
Background Xenograft kidney transplantation has been receiving increasing attention. The purpose of this study is to use bibliometric analysis to identify papers in this research field and explore their current status and development trends.Methods Using the data in the Web of Science core database from Clarivate Analytics as the object of study, we used ‘TS = Kidney OR Renal AND xenotransplantation’ as the search term to find all literature from 1980 to 2 November 2022.Results In total, 1005 articles were included. The United States has the highest number of publications and has made significant contributions in this field. Harvard University was at the forefront of this study. Professor Cooper has published 114 articles in this field. Xenotransplantation has the largest number of relevant articles. Transplantation was the most cited journal. High-frequency keywords illustrated the current state of development and future trends in xenotransplantation. The use of transgenic pigs and the development of coordinated co-stimulatory blockers have greatly facilitated progress in xenotransplantation research. We found that ‘co-stimulation blockade’, ‘xenograft survival’, ‘pluripotent stem cell’, ‘translational research’, and ‘genetic engineering’ were likely to be the focus of attention in the coming years.Conclusions This study screened global publications related to xenogeneic kidney transplantation; analyzed their literature metrology characteristics; identified the most cited articles in the research field; understood the current situation, hot spots, and trends of global research; and provided future development directions for researchers and practitioners.